2002
DOI: 10.1113/jphysiol.2001.013469
|View full text |Cite
|
Sign up to set email alerts
|

Activation and sensitisation of low and high threshold afferent fibres mediated by P2X receptors in the mouse urinary bladder

Abstract: It has been proposed that extracellular ATP may be involved in visceral mechanosensory transduction by activating ligand‐gated ion channels (P2X receptors). In this study, we have investigated the effects of the P2X3 agonist α,β‐methylene ATP (α,β‐meATP) and antagonist 2′,3′‐O‐trinitrophenyl‐ATP (TNP‐ATP) on pelvic afferents innervating the urinary bladder using an in vitro mouse bladder‐pelvic nerve preparation. Intravesical application of α,β‐meATP (0.03‐1 mm) increased multifibre discharges in a concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
178
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(193 citation statements)
references
References 34 publications
9
178
1
3
Order By: Relevance
“…The altered P2X receptor expression accounts for greater current density in response to purinergic agonists, and likely contributes to the slowed desensitization kinetics of the slow desensitizing current after bladder inflammation. Considering the reported mechanosensory role for homomeric P2X 3 and P2X 2 and heteromeric P2X 2/3 receptors (Cockayne et al 2000(Cockayne et al , 2005Rong et al 2002;Vlaskovska et al 2001), and the increased urothelial release of ATP during inflammation (Sun et al 2001), the present findings suggest that the altered expression of P2X receptors contributes to the enhanced responses of bladder neurons during cystitis.…”
Section: Discussionmentioning
confidence: 92%
“…The altered P2X receptor expression accounts for greater current density in response to purinergic agonists, and likely contributes to the slowed desensitization kinetics of the slow desensitizing current after bladder inflammation. Considering the reported mechanosensory role for homomeric P2X 3 and P2X 2 and heteromeric P2X 2/3 receptors (Cockayne et al 2000(Cockayne et al , 2005Rong et al 2002;Vlaskovska et al 2001), and the increased urothelial release of ATP during inflammation (Sun et al 2001), the present findings suggest that the altered expression of P2X receptors contributes to the enhanced responses of bladder neurons during cystitis.…”
Section: Discussionmentioning
confidence: 92%
“…Using experiments, Burnstock demonstrated that when a hollow viscus (such as the intestine, ureter, and bladder) was extensively distended and overfilled, the epithelial cells in the cavity would be stimulated to release ATP, which would subsequently activate the P2X 3 and P2X 2/3 receptors in the subepithelial nerve endings to generate action potentials [25]; this change corresponds to hyperexcitability of the sensory neurons, and the action potentials would be transmitted to the central nervous system, resulting in a colicky sensation [26,27]. In this study, the method of colorectal balloon distention was used to prepare an animal model of IBS visceral hyperalgesia in rats, and the expression of the P2X 3 receptor in the colon myenteric plexus of the rats in the IBS model group was found to be higher than that of the rats in the normal group.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, when DIDS, an inhibitor of ecto-ATPase 13 , was infused intravesically, the following application of ATP (pH 6.0) induced detrusor overactivity without pre-infusion of PS. Rong et al also showed that intravesical application of α,β-methylene ATP increased multifiber discharges in the mouse bladder, suggesting that α,β-methylene ATP can penetrate the urothelium 14 . Taken together, it is assumed that ATP (pH 6.0) with co-application of DIDS or α,β-methylene ATP can penetrate bladder epithelium to induce detrusor overactivity without changing urothelial permeability and that, in addition to urothelial barrier function, ecto-ATPase activity in the urothelium also contributes to the suppression of ATP-induced detrusor overactivity.…”
Section: Commentmentioning
confidence: 99%